2018
DOI: 10.1097/pec.0000000000001675
|View full text |Cite
|
Sign up to set email alerts
|

Does Receiving a Text Message Reminder Increase Follow-up Compliance After Discharge From a Pediatric Emergency Department?

Abstract: Objectives: Compliance with recommended follow-up from the pediatric emergency department (PED) has been shown to be poor. This study evaluated whether a text message reminder to the caregivers after discharge from the PED improved compliance with recommended primary care follow-up.Methods: This was a blinded randomized control trial conducted at a level 1 pediatric trauma center. The intervention was a text message sent to the caregiver within 24 hours of discharge from the PED reminding them to follow up wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…For example, follow‐up appointments scheduled from the ED, 43 intensive asthma education, 44 and monetary incentives 45 may improve follow‐up among children discharged from the ED with asthma. Other studies have suggested that follow‐up phone calls and care coordination efforts may improve follow‐up 46,47 and reduce potentially unnecessary ED visits, 47,48 whereas text messaging and email communications may be of more limited value 49,50 …”
Section: Discussionmentioning
confidence: 99%
“…For example, follow‐up appointments scheduled from the ED, 43 intensive asthma education, 44 and monetary incentives 45 may improve follow‐up among children discharged from the ED with asthma. Other studies have suggested that follow‐up phone calls and care coordination efforts may improve follow‐up 46,47 and reduce potentially unnecessary ED visits, 47,48 whereas text messaging and email communications may be of more limited value 49,50 …”
Section: Discussionmentioning
confidence: 99%
“…We found that an automated self‐scheduling text and phone messaging system improved follow‐up attendance at 30 and 120 days after discharge from the ED. Previous studies examining automated reminders to improve follow‐up adherence have mixed results 11–13 . A pediatric ED study using SMS appointment reminders found no improvement in follow‐up to primary care within 17 days of discharge 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining automated reminders to improve follow‐up adherence have mixed results 11–13 . A pediatric ED study using SMS appointment reminders found no improvement in follow‐up to primary care within 17 days of discharge 11 . Another ED study focusing on patients with a specific diagnosis found that SMS appointment reminders improved follow‐up rates by 28.3% for urgent referral to primary care providers 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations